PENGARUH KOORDINASI DAN PRESTASI KERJATERHADAP KINERJA GURU MTSN KOTA TANJUNG BALAI DI ERA COVID 19: Influence of Coordination and Work Performance on Teacher Work Performance in Madrasah Tsanawiyah State Of Tanjungbalai City, Thesis, 2022 - Hafiz, Rizlan (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2023)
This research aims to find out (1) to find out the influence of coordination on the work performance of teachers in Madrasah Tsanawiyah State Of Tanjungbalai City. (2) To find out the influence of teacher work performance on the work performance of teachers in Madrasah Tsanawiyah State Of Tanjungbalai City. (3) To find out the influence of coordination and The population in this study is all permanent teachers of Civil Servants who are in Tsanawiyah State Tanjungbalai city which numbers 51 teachers. The calculation of the analysis test in this study was conducted using the help of the Statistical Package for Social Science (SPSS) program. Based on the results of the study that (1) coordination has a significant effect on the work performance of teachers in Madrasah Tsanawiyah State Of Tanjungbalai City. This is characterized by the value given X1 (coordination) to Y (teacher work performance) of 12,70 % and positive means that the greater the coordination carried out by the principal of Madrasah Tsanawiyah State Of Tanjungbalai City (X1) the greater the work performance of teachers (Y). tcount at X1 = 2,129 > ttable (0.05;49) = 0.2329 or by comparing the value of sig = 0.001 < error level of 5% = 0.05. (2) The work performance of teachers has a significant effect on the performance of teachers in Madrasah Tsanawiyah State of Tanjungbalai City. This is characterized by a value of X2 (teacher work performance) against Y (teacher work performance) of 13,5 % and positive means that the greater the teacher's work performance (X2) the greater the teacher's work performance (Y). tcount at X2 = 2,231 > ttable (0.05;49) = 0.2329 or by comparing the value of sig= 0.000 < error level of 5% = 0.05. (3) The coordination variable and work performance of teachers had an effect of 21,10 % on the performance of teachers in Madrasah Tsanawiyah State Of Tanjungbalai City. Simultaneously coordination and work performance have a low effect on the work performance of teachers in Madrasah Tsanawiyah State Of Tanjungbalai City